LIGHTING DESIGN OF ENERGY EFFICIENT BUILDING IN OFFICE BUILDING - Nurul Jamala; Idawarni Asmal; Syavir Latif; Syahriana Syam (International Conference on Coastal and Delta Areas, 2015)
Climate change led to the issue of global warming and have an impact also on increasing energy load of the building. The designer Architect instrumental in designing buildings with attention to environmental impact, namely temperature, wind and light. Solar radiation causing the high load of electrical energy for air conditioning, so the Architects as the designer should be able to minimize the radiation of heat into the building. In addition, the sunlight will be able to enter into the building so that the load of the electrical energy for the artificial lighting can be minimized as well. Energy efficient building design is a great thing to note, with consideration of comfort in activities so that an increase in labor productivity. The purpose of this research is to analyze the lighting in the Office building of the Wisma Kalla in Makassar. Energy-efficient architecture is based on the idea of minimising energy use without limit or change the function of the building, comfort, and productivity of the user space. This research analyzes the energy load of electric lighting setting design appropriate spaces with attention to the standard level of illumination is recommended. Quantitative research methods using ecotect program to find out the values of illumination and energy consumption on used point lights. Results of the study concluded that the utilization of natural lighting can minimize the load on the building energy consumption but taking into account the recommendations of the standard illumination on the work space Office.Key words: Energyefficient , Office building, Lighting